Understanding and modelling the thermodynamics and electrochemistry of lithiation of tin (IV) sulfide as an anode active material for lithium ion batteries. (10th April 2021) - Cupid, Damian M.; Rezqita, Arlavinda; Glibo, Albina; Artner, Martin; Bauer, Viktor; Hamid, Raad; Jahn, Marcus; Flandorfer, Hans
Highlights: Lix SnS2 is a metastable phase which forms during lithiation of SnS2 . The metastable nature of Lix SnS2 is confirmed by thermodynamic modelling. The lithiation of SnS2 under equilibrium conditions is a single-phase process. The calculated metastable Li–S–Sn phase diagram confirms the above observations. Abstract: Tin (IV) sulfide is a promising anode active material for lithium ion batteries due to its relatively high reversible capacity of 644 mAh/g, which is more than one and a half times that of graphite. During lithiation of tin (IV) sulfide, an inert Li2 S matrix is formed in the first discharge cycle, which serves to accommodate the mechanical stresses associated with the volume expansion of tin during the successive Lix Sn alloying and de-alloying reactions. In order to improve the electrochemical performance of tin (IV) sulfide further, fundamental understanding and insights into the thermodynamics, phase formation, and driving forces for the lithiation reactions are still required. Therefore, in this work, a computational thermodynamics approach was combined with ex-situ XRD investigations of electrodes during the discharge reaction as well as galvanostatic intermittent titration technique (GITT) experiments in order to clarify the lithiation thermodynamics of tin (IV) sulfide. Based on the experimental data, a one-phase mechanism was suggested for the intercalation of lithium into SnS2, a thermodynamic model was developed to describe the intercalation reaction and the expected open circuit voltages were calculated. Graphical abstract: Image, graphical abstract